QUALITY ASSESSMENT ON INSTANT PORRIDGE OF SNAKEHEAD (Channa striata) FISH PROTEIN CONCENTRATE FLOUR FORTIFIED WITH Chlorella sp. DURING STORAGE AT ROOM AND COLD TEMPERATURES - Josua, Victor; Sari, N Ira; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research aimed to assess the quality of instant porridge snakehead (Channastriata) fish protein concentrate (FPC) fortified with Chlorella sp. flour during storage atroom and cold (5 0C) temperature. This experimental research was began with preparing FPCinstant porridge added with 2% Chlorella sp. flour and then stored at room (B1) and cold (B2)temperature and observed the quality changes during storage on 0, 7, 14, 21, 28 days. Qualityparameters assessed were the proximate analysis, peroxide value, total of mold and sensoryanalysis. The results of quality assessment of instant porridge during storage showed that thewater content, fat content, peroxide value and total mold colonies on both B1 and B2treatments at the beginning up to the end of the storage were 6.99 - 7.30 %; 3.63 - 4.28%;11.97 - 5.98 meq / 1000 g; and 1,8x102 - 1,3x102 cfu/g, respectively. The sensory evaluationshowed no difference in the appearance and consistency but there was a difference in aromaon B2 which tend to be rancid.Keywords : Instan porridge, fish protein concentrate, quality